On some problems of analysis and assessment of the influence of the human factor on the safety of technical systems - D. I. Lobach (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The purpose of the theoretical research of the article is to formulate and describe cases in which it is possible to conduct correlation and other types of analysis for some situations to quantify the impact of the human factor on safety of technical systems using plausible patterns and statistical distributions, to consider some problems and reliability issues that arise in the course of solving such problems.Method. Some cases of possible application of the chi-square distribution to assess the impact of the human factor on safety of systems with the participation of people in technological operations are presented.Result. Approach on using of agreement criterium of chi-square, explanations and recommendations on the implementation of expert research in this area are offered for analysis and assessment.Conclusion. The article considers the conditions and describes the possibilities for carrying out some types of analysis in assessing the impact of the human factor on the functioning of technical systems.